PENGARUH KUALITAS PRODUK, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (STUDI KONSUMEN UMKM MIE AYAM DAN BAKSO BAROKAH INA KABUPATEN BUNGO) - Delila Fitri Harahab; Yuniar Mryanti; Herawati Herawati (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
This study aims to analyze the influence of product quality, price and location on purchasing decisions of the UMKM consumer study of Mie Ayam and Bakso Barokah Ina in Bungo. The research method used is quantitative, the data sources used are primary and secondary data. The population in this study were all consumers who had bought at Mie Ayam and Bakso Barokah Ina stalls in Bungo. The sample in this study as many as 96 respondents with sampling taken by using accidental sampling technique. Data collection methods used: interviews and questionnaires. The data analysis method used is multiple linear analysis and hypothesis testing using t test, F test and coefficient of determination. From the results of the t-test analysis shows that product quality, price and location partially affect purchasing decisions. The results of the F-test show that product quality, price and location simultaneously affect purchasing decisions. The results of the analysis of the coefficient of determination obtained adjusted R square (R2) of 0.670, this means that 67% of changes in purchasing decisions are caused by the changes in product quality, price and location variables. While the remaining 33% is due to changes in other variables included in the variables studied